ANALISES OF MOTOR BEHAVIOR OF LOW VISION SCHOLARS FROM 7 TO 10 YEARS OLD FROM STATE PUBLIC SCHOOL IN THE MUNICIPAL DISTRICT OF MACAPÁ / AP: CASE (Fiep Bulletin - online, 2011)
This study aims at to analyze the scholars' Motor Behavior (CM) with Visual Deficiency(DV), Low Vision (BV), aged between 7 to 10. The sample was composed by five scholars, 3 girls and 2 boys, belonging to a State Elementary School, between first and fourth grades, of the municipal district of Macapá / AP that participated in Physical Education classes. A questionnaire of life habits was applied, and in order to assess the CM, Rosa Neto´s (2002), Scale of Motor Development (EDM) was used to evaluate the following elements of human motricity: fine motricity, global motricity, balance, corporal outline, space organization, temporal organization and laterality. The tests have progressive degree of difficulty, the student executes until they are not able to accomplish the proposed test or finish all of them. The individual's motor age (IM) corresponds to the test of larger degree than was accomplished. From data regarding Chronological Age (IC) and IM expressed in months, the Motor Quotient(QM) was calculated in order to classify the students tested in an EDM, that varies from very superior to the very inferior. After the analysis, it was verified that for the five scholars, the average of general IM is 88 months, and general QM is 92 months. In EDM the obtained results were: normal medium 02, normal low 01, inferior 01 and normal high 01, demonstrating that the group presents a good motor quotient, with a deficit found in the child that presented minor motor activity everyday habits. That reinforces the data found in the literature that highlights the importance of motor experiences. The inclusion of DV scholars in the physical education classes should be motivated and accomplished effectively for the contribution this participation may bring.
Keywords: Motor behavior; low vision; motor evaluation